Isolation and Partial Characterization of Surface Producing Bacterial Strain Producing Amylase from Soil - Sharma, Samriti; Guleria, Shiwani; Behl, Arvind; Batra, Navneet (International Journal of Bio-resource and Stress Management, 2018)
Starch is an important constituent of the human diet and is a major storage product of many economically important crops such as wheat, rice, maize, tapioca, and potato. The production of α-amylase is essential for conversion of starches into oligosaccharides. Amylase is one of the most important enzymes used in industry such as in textile, food, paper and pharmaceutical industry etc. Amylase has ability to hydrolyzed starch molecules into polymer composed of glucose unit. The aim of present study was to isolate amylase producing bacteria from soil samples, screening of amylase producing strains, morphological and biochemical characterizations of strains, and optimized cultural conditions of the strains. The soil samples were collected from deep soil of campus at Chandigarh with the help of aseptic spectula. The bacterial strains were isolated by serial dilution and plating method. Three bacterial strains such as RT03, RT5 and T5 having amylolytic activity was isolated. Based on intensity of clear zone one strain were selected for further study. The morphological characterization of strain RT5 showed that it is rod shaped bacilli, cream color, raised elevation, entire margin, moderate size and Gram negative in nature. Enzymatic activity of strain RT5 was estimated at various pH (6, 7 and 8) and temperatures (30 °C, 37 °C, 50 °C and 60 °C). The best amylolytic activity of RT5 was observed at pH 6 with optimum temperature 50 °C.